ALKBH5 inhibitors as a potential treatment strategy in heart failure—inferences from gene expression profiling - Komal, Sumra; Gohar, Atia; Althobaiti, Saad; Ahmad Khan, Ishtiaq; Cui, Liu-Gen; Zhang, Li-Rong; Han, Sheng-Na; Shakeel, Muhammad (Frontiers in Cardiovascular Medicine, 2023)
Heart Failure (HF) is a complex clinical syndrome in which the heart is unable to provide enough blood flow to meet metabolic needs and lacks efficient venous return. HF is a major risk factor for morbidity and mortality with cardiovascular diseases globally. Despite enormous research, the molecular markers relevant to disease prognosis and management remain not well understood. Here, we analyzed the whole transcriptomes of 18 failing hearts and 15 non-failing hearts (predominantly of Caucasian origin), by applying the standard in silico tools. The analyses revealed novel gene-markers including ALKBH5 of mRNA demethylation and KMT2E of histone modification processes, significantly over-expressed in the HF compared with the non-failing hearts (FDR<0.05). To validate the over-expression of ALKBH5, we determined the global m 6 A level in hypoxic H9c2 cells using a dot blot assay. The global m 6 A level was found markedly lower in the hypoxic H9c2 cells than in the control cells. Additionally, the expression of ALKBH5 in the H9c2 cells was quantified by the qPCR and found to be 1.18 times higher at 12 hr (P<0.05), and 1.67 times higher at 24 hr of hypoxia (P<0.01) compared with the control cells, indicating a likely role of ALKBH5 in the failing cardiac cells. Furthermore, we identified several compounds through the virtual screening of 11,272 drug-like molecules of the ZINC15 database to inhibit the ALKBH5 in a molecular docking process. Collectively, the study revealed novel markers potentially involved in the pathophysiology of HF and suggested plausible therapeutic molecules for the management of the disease.